A laboratory analysis of the Kura‐Araxes pottery from Tepe Pirtaj using petrography and XRF techniques. (24th January 2022) - Sharifi, Mahnaz; Omrani, Behrouz
Abstract: Sounding at the archaeological site of Tepe Pirtaj in Bijar of Kurdistan aimed to investigate the foremost cultural phenomenon of the third millennium bce across the Near East, namely the Kura‐Araxes culture, in the eastern Central Zagros, as the site promised to provide important insights into the spread of the culture in an easternmost tract of the Central Zagros. Characterized by a grey body often bearing incised decorations, the Kura‐Araxes material from Pirtaj shows high expertise in manufacture. The present study explored the pottery technology and manufacturing by selecting a sample of 12 sherds for petrographic and X‐ray fluorescence (XRF) analyses. The main objective was to examine the composition and structure, differences and comparisons, firing temperature and origin (local or imported) of the ceramics. This is of particular significance given the dearth of contemporaneous sites in Bijar. Petrographic and XRF analyses showed the ceramics to be indigenous to the region and, thus, locally produced. The whole sample was found to have been fired at temperatures below 800°C. Geological data attest to the abundance of slate, lime, quartz and calcite in the regional mountains and sediments. Thus the ceramics were locally produced, though some slight differences are discernible as regards technological aspects.